The benefits of lower ozone due to air pollution emission reductions (2002–2011) in the Eastern United States during extreme heat. (1st February 2020) - Loughner, Christopher P.; Follette-Cook, Melanie B.; Duncan, Bryan N.; Hains, Jennifer; Pickering, Kenneth E.; Moy, Justin; Tzortziou, Maria
ABSTRACT: Using the Community Multiscale Air Quality (CMAQ) model and the Benefits Mapping and Analysis Program – Community Edition (BenMAP-CE) tool, we estimate the benefits of anthropogenic emission reductions between 2002 and 2011 in the Eastern United States (US) with respect to surface ozone concentrations and ozone-related health and economic impacts, during a month of extreme heat, July 2011. Based on CMAQ simulations using emissions appropriate for 2002 and 2011, we estimate that emission reductions since 2002 likely prevented 10– 15 ozone exceedance days (using the 2011 maximum 8-hr average ozone standard of 75 ppbv) throughout the Ohio River Valley and 5– 10 ozone exceedance days throughout the Washington, DC – Baltimore, MD metropolitan area during this extremely hot month. CMAQ results were fed into the BenMAP-CE tool to determine the health and health-related economic benefits of anthropogenic emission reductions between 2002 and 2011. We estimate that the concomitant health benefits from the ozone reductions were significant for this anomalous month: 160–800 mortalities (95% confidence interval (CI): 70–1, 010) were avoided in July 2011 in the Eastern U.S, saving an estimated $1.3–$6.6 billion (CI: $174 million–$15.5 billion). Additionally, we estimate that emission reductions resulted in 950 (CI: 90–2, 350) less hospital admissions from respiratory symptoms, 370 (CI: 180–580) less hospital admissions for pneumonia, 570 (CI: 0–1650) less Emergency Room (ER) visits from asthma symptoms, 922, 020 (CI: 469, 960–1, 370, 050) less minor restricted activity days (MRADs), and 430, 240 (CI: −280, 350–963, 190) less symptoms of asthma exacerbation during July 2011. Implications : We estimate the benefits of air pollution emission reductions on surface ozone concentrations and ozone-related impacts on human health and the economy between 2002 and 2011 during an extremely hot month, July 2011, in the eastern United States (US) using the CMAQ and BenMAP-CE models. Results suggest that, during July 2011, emission reductions prevented 10-15 ozone exceedance days in the Ohio River Valley and 5-10 ozone exceedance days in the Mid Atlantic; saved 160-800 lives in the Eastern US, saving $1.3 - $6.5 billion; and resulted in 950 less hospital admissions for respiratory symptoms, 370 less hospital admissions for pneumonia, 570 less Emergency Room visits for asthma symptoms, 922, 020 less minor restricted activity days, and 430, 240 less symptoms of asthma exacerbation.